2003
DOI: 10.1093/annonc/mdg118
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel and carboplatin is an active regimen in advancednon-small-cell lung cancer: a phase II study in Caucasian and Asian patients

Abstract: This regimen is active in advanced NSCLC. The potential impact of ethnicity on efficacy and toxicity of treatment requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 19 publications
4
71
0
1
Order By: Relevance
“…The probability of developing neutropenia varies for each individual regimen; currently, predictions are based on the treatment regimen used and the experience of the attending physician (Sato et al, 2012 anticancer drugs (Lyman and Delgado, 2003;Millward et al, 2003;Timmer-Bonte et al, 2005). By contrast, few investigations have examined the predictive factors for neutropenia after docetaxel-based systemic chemotherapy in patients with CRPC.…”
Section: Predictive Factors For Neutropenia After Docetaxel-based Sysmentioning
confidence: 99%
“…The probability of developing neutropenia varies for each individual regimen; currently, predictions are based on the treatment regimen used and the experience of the attending physician (Sato et al, 2012 anticancer drugs (Lyman and Delgado, 2003;Millward et al, 2003;Timmer-Bonte et al, 2005). By contrast, few investigations have examined the predictive factors for neutropenia after docetaxel-based systemic chemotherapy in patients with CRPC.…”
Section: Predictive Factors For Neutropenia After Docetaxel-based Sysmentioning
confidence: 99%
“…We were interested in the activity of the combination of docetaxel and carboplatin as second-line treatment in NSCLC patients, who were treated with platinum or non-platinum-containing regimens as first-line therapy. In chemotherapy-naive patients the combination of docetaxel and carboplatin was active with response rates between 27 and 44%, and acceptable toxicity [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…overall treatment efficacy was favorable, but was not enhanced by COX-2 inhibitors in terms of tumor response (36.0%), OS (13.7 months) and 1-year survival ratio (56.0%). Previous phase II-III trials of docetaxel and carboplatin without COX-2 inhibitors for advanced NSCLC demonstrated that the ORR, OS and 1-year survival rate were 16.0-55.0%, 9.0-13.9 months and 44.0-58.0%, respectively (15,(18)(19)(20). The incidence of adverse events, such as grade 3/4 neutropenia (80.0%) and febrile neutropenia (8.0%), was similar to those previously reported (51.1-79.0 and 3.3-26.0%, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…Taxanes are able to drive COX-2 expression, which is followed by increased prostaglandin E 2 (PGE 2 ) production (14); therefore, a complementary and additive or synergistic effect with COX-2 inhibitors may be expected. Moreover, the response to carboplatin plus docetaxel in Asian patients was reported to be statistically superior to that in Caucasian patients (15).…”
Section: Introductionmentioning
confidence: 98%